PHYSICAL FITNESS ATTRIBUTES, VITAMIN D, DEPRESSION, AND BMD IN OMANI’S CHILDREN - Hashem Kilani; Saif Alyaarubi; Kashef Zayed; Ibrahim Alzakwani; Hadia Bererhi; Raghda Shukri; Khalid Alrasadi (European Scientific Journal, ESJ, 2013)
Physical fitness attributes, vitamin D, depression, and BMD in Omani’s Children 9-12 years old were investigated in 54 girls and 42 boys (average age of 12.9 ± 1.6) to assess health related fitness, body composition. Eighty two percent of the females and forty two percent of the males were deficient in vitamin D (<50 nmol/L). Those females deficit in vitamin D were associated with higher fat percentage compared to those with normal vitamin D status. There were no significant differences in all physical exercise attribute scores (p > 0.05) in females between those with normal and those with low vitamin D levels. These results were also replicated in males except for grip and cardio-respiratory components. Initial analysis also indicates that the prevalence of symptoms of depression among Omani children was 32% ranging from mild to severe depression with negative correlation with vitamin D deficiency is significant at the 0.01 level (-0.353 2-tailed). The females are deficient in vitamin D, might be susceptible to the early diagnosis of osteoporosis and depression due to their deficiency. Children should be involved in physical activity program and meet the required sunlight exposure during all season to gain a healthy lifestyle.